Clinical procedures in primary eye care - Elliott, David B. (Philadephia Elsevier, 2020)
"Well organized and easy to read, Clinical Procedures in Primary Eye Care, 3rd th Edition, takes an accessible, step-by-step approach to describing the commonly used primary care procedures that facilitate accurate diagnosis and effective patient management. This practical, clinically-focused text offers succinct descriptions of today's most frequently encountered optometric techniques supported by research-based evidence. You'll find essential instructions for mastering the procedures you need to know, including recent technical advances in the field.."--
Previous edition: Philadelphia : Saunders, 2014.
Keywords: Eye -- Examination; Eye -- Diseases -- Diagnosis; Vision Disorders -- diagnosis; Ocular Motility Disorders -- diagnosis; Optometry -- methods; Vision Disorders -- therapy; Vision Tests -- methods; Eye -- Diseases -- Diagnosis; Eye -- Examination